RECONSTRUCTION OF VALUE EDUCATION IN ISLAMIC ELEMENTARY SCHOOL (A CRITICAL ANALYSIS IN CONTEMPORARY EDUCATION) - Ahmad Shofiyuddin Ichsan (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2023)
This study aimed to find out the importance of value education to be reconstructed in Elementary School in the contemporary education. This study was a library research with descriptive exploratory based on the results of reflective evaluations from the relevant sources and reinforced by field studies from researcher directly. The study results revealed that the increasingly widespread the mischief of Elementary School students provided an open space to reconstruct the value education. So, it was necessary to take steps in implementing value education including the program routine of